The Relationship Between Intercultural Communicative Competence and English Language Learning Outcomes - Restuti Retno Ningrum; Abdul Halim; Ade Ismail Ramdhan Hamid (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to investigate the relationship between Intercultural Communicative Competence (ICC) and English learning results among 57 first-year students at a private university in East Kalimantan. ICC is viewed as an essential element in language learning since it involves cultural awareness, communication abilities, and an open attitude that promotes successful intercultural exchanges. This research employed a quantitative approach that utilized two primary tools: an ICC survey grounded in Byram’s (1997) model and an English proficiency assessment through the British Council EnglishScore application. Statistical analyses through Pearson correlation and multiple linear regression demonstrated a strong and significant positive relationship between ICC and English proficiency (r = 0.632, p < 0.001). Among the elements of the ICC, attitudes demonstrated the strongest correlation, with skills and knowledge following next. These findings underscore the significance of nurturing students’ intercultural attitudes like openness, empathy, and adaptability since they greatly improve English learning results. This study offers valuable guidance for English teachers and curriculum designers, highlighting the importance of incorporating intercultural learning experiences into language teaching to enhance learners' readiness for effective communication in varied global situations.